2016
DOI: 10.1007/s00590-016-1765-z
|View full text |Cite
|
Sign up to set email alerts
|

Double locking plate fixation for femoral shaft nonunion

Abstract: Because of the high union rates and lack of significant complications in our series, double locking plate fixation can serve as an effective method of addressing femoral shaft nonunions. No significant complications were found postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…13 Research advocating plate replacement indicates that although the plate has the disadvantage of secondary trauma during surgery, it can achieve the aim of radical debridement, correction of deformities and full bone grafting. 17 Our experience supports the use of a locking plate combined with structural autogenous ilium grafting to treat nonunion after plate installation because it maximizes osteoconductive, osteogenic and osteoinductive properties of autologous bone, resulting in bone healing rates reaching 97.1%. 3 However, some treatments fail due to the span of the graft being large and the exterior plate being unable to provide sufficient stability for anterior bone grafting.…”
Section: Discussionsupporting
confidence: 61%
“…13 Research advocating plate replacement indicates that although the plate has the disadvantage of secondary trauma during surgery, it can achieve the aim of radical debridement, correction of deformities and full bone grafting. 17 Our experience supports the use of a locking plate combined with structural autogenous ilium grafting to treat nonunion after plate installation because it maximizes osteoconductive, osteogenic and osteoinductive properties of autologous bone, resulting in bone healing rates reaching 97.1%. 3 However, some treatments fail due to the span of the graft being large and the exterior plate being unable to provide sufficient stability for anterior bone grafting.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, augmented fixation with additional medial plate is a standard procedure associated with high union rates and no significant postoperative complications . Double plating technique is recommended by many authors for cases where single plate use is not adequate .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the double-plate fixation is emerging as a reasonable alternative to treat the nonunion. A union rate above 90% has been reported in studies [ 18 20 ], but double-plate fixation principle has never been proposed. In 2015, Maimaitiyiming et al [ 18 ] reported 14 consecutive patients with femoral shaft aseptic nonunion were treated with double-plate fixation combined with bone grafting and all cases achieved bony union in the average time of 5.2 months.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that implants should be placed on the lateral and anterior sides, at a 90° angle with each other. In 2016, Peng et al [ 20 ] demonstrated that double locking plates fixation could serve as an effective therapy strategy for femoral shaft nonunion. Jiang et al [ 19 ] got the union rate of 100% by using the fibular autograft with double locking plates for the treatment of diaphyseal femoral nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation